DOI: 10.14264/uql.2016.1101
|View full text |Cite
|
Sign up to set email alerts
|

Clinical supervision, burnout and intent to leave: an Australian mixed methods study of community-based allied health professionals

Abstract: ObjectiveClinical supervision is widely recognised for providing professional support, professional development and clinical governance for healthcare workers. Despite the growing uptake of clinical supervision, there have been few studies about the effectiveness of supervision for allied health professionals and fewer studies conducted within the Australian health context. This study aims to identify the perceived effectiveness of clinical supervision of allied health professionals in an Australian metropolit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 172 publications
1
16
0
Order By: Relevance
“…The MCSS-26 results showed that finding time was a barrier to effective clinical supervision and is consistent with previous findings [7, 11, 12, 1417]. Allied health professionals who report difficulty finding time for clinical supervision also report higher levels of emotional exhaustion [47]. Hence, this issue is a concern for allied health departments and may have wider implications including a negative impact on patient care [10].…”
Section: Discussionsupporting
confidence: 83%
“…The MCSS-26 results showed that finding time was a barrier to effective clinical supervision and is consistent with previous findings [7, 11, 12, 1417]. Allied health professionals who report difficulty finding time for clinical supervision also report higher levels of emotional exhaustion [47]. Hence, this issue is a concern for allied health departments and may have wider implications including a negative impact on patient care [10].…”
Section: Discussionsupporting
confidence: 83%
“…Twenty-seven quantitative , two qualitative [49,50] and three mixed methods studies [51][52][53] were included in the review. Fifteen studies used a randomised controlled (n = 1) [22] or quasi-experimental design (n = 14) [23][24][25][26][27][28][29][30][31][32][33][34][35]51] to establish the effect of clinical supervision on organisational outcomes.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Fifteen studies used a randomised controlled (n = 1) [22] or quasi-experimental design (n = 14) [23][24][25][26][27][28][29][30][31][32][33][34][35]51] to establish the effect of clinical supervision on organisational outcomes. Eight studies investigated the association between effectiveness of clinical supervision and organisational outcomes [37][38][39][40][41][42][43]52]. Eight studies investigated the association between the effectiveness of the supervisor and organisational outcomes [32,36,39,41,43,45,46,48].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations